Coaching and Mentoring First-Year and Student Teachers. - Denmark, Vicki (Taylor and Francis, 2013)
Features over 60 step-by-step procedures, checklists, and planning guides for supervisors, mentors, and all those engaged in in-service teacher training. NEW to this edition: updated coverage of standards, assessment, analyzing student work, cognitive coaching, and more.